Study on Viscoelastic Properties of Asphalt Mixtures Incorporating SBS Polymer and Basalt Fiber under Freeze–Thaw Cycles - Wang, Wensheng (Polymers (Basel), 2020)
This study aims to study the viscoelastic properties of asphalt mixtures incorporating styrene–butadiene–styrene (SBS) polymer and basalt fiber under freeze–thaw (F-T) cycles by using the static creep test. Asphalt mixture samples incorporating styrene–butadiene–styrene (SBS) polymer and basalt fiber were manufactured following the Superpave gyratory compaction (SGC) method and coring as well as sawing. After 0 to 21 F-T cycles processing, a uniaxial compression static creep test for the asphalt mixture specimens was performed to evaluate the influence of F-T cycles. The results indicated that the F-T cycles caused a larger creep deformation in the asphalt mixtures, which led to a decrease in the rut resistance of the asphalt mixtures incorporating SBS polymer and basalt fiber. Besides, the resistance to deformation decreased significantly in the early stage of F-T cycles. On the other hand, the viscoelastic parameters were analyzed to discuss the variation of viscoelastic characteristics. The relaxation time increased with F-T cycles, which will not be conducive to internal stress dissipation. Compared with lignin fiber, basalt fiber can improve the resistance to high-temperature deformation and the low-temperature crack resistance of asphalt mixtures under F-T cycles.